The shadow of your smile [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Deep Haven novel., 2012)
A beautiful blanket of snow may cover the quaint town of Deep Haven each winter, but it can't quite hide the wreckage of Noelle and Eli Hueston's marriage. After twenty-five years, they're contemplating divorce . . . just as soon as their youngest son graduates from high school. But then an accident erases part of Noelle's memory. Though her other injuries are minor, she doesn't remember Eli, their children, or the tragedy that has ripped their family apart. What's more, Noelle is shocked that her life has turned out nothing like she dreamed it would. As she tries to regain her memory and slowly steps into her role as a wife and mother, Eli helps her readjust to daily life with sometimes-hilarious, sometimes-heartwarming results. But can she fall in love again with a man she can't remember? Will their secrets destroy them . . . or has erasing the past given them a chance for a future?